A CRISPR-Cas12a-based diagnostic method for multiple genotypes of severe fever with thrombocytopenia syndrome virus. - Bum Ju Park; Jeong Rae Yoo; Sang Taek Heo; Misun Kim; Keun Hwa Lee; Yoon-Jae Song (Public Library of Science (PLoS), 2022)
Severe fever with thrombocytopenia syndrome virus (SFTSV) infection is commonly reported in countries of Northeast Asia including China, Japan and South Korea. The majority of the SFTS patients are elderly and the average fatality rate is more than 10%. A rapid and sensitive diagnostic method to monitor and prevent SFTSV transmission remains an urgent clinical challenge. In this study, we developed a molecular diagnostic technique for detection of SFTSV using the CRISPR-Cas12a system combined with reverse transcription recombinase polymerase amplification (RT-RPA). Using this method, we successfully diagnosed SFTSV infections with the reaction time of 50 min from blood plasma without cross-reactivity to other viruses, supporting its application for rapid and sensitive diagnosis of SFTS.